2014
DOI: 10.1111/1753-0407.12163
|View full text |Cite
|
Sign up to set email alerts
|

Decreased miR‐146 expression in peripheral blood mononuclear cells is correlated with ongoing islet autoimmunity in type 1 diabetes patients 1型糖尿病患者外周血单个核细胞miR‐146表达下调与胰岛持续免疫失衡相关

Abstract: The results suggest that dysregulation of miR-146 expression in PBMC may be associated with the ongoing autoimmune imbalance in T1D patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 34 publications
6
88
4
2
Order By: Relevance
“…Downregulation of miR-146b-5p in PBMC from T1D patients has been described before [168], but we did not detect a deviation of miR-146b-5p in serum from T1D patients, and to our knowledge it has not been reported by any other another study. For miR-151, it seems likely that this miRNA has a relation to metabolic processes, since it has been connected to mitochondrial activity [227], and decreased serum levels of both miR-151a-3p and -5p have been demonstrated after exercise [228].…”
Section: Mirnas Associated To Glucose Homeostasis Within the High-riscontrasting
confidence: 65%
See 1 more Smart Citation
“…Downregulation of miR-146b-5p in PBMC from T1D patients has been described before [168], but we did not detect a deviation of miR-146b-5p in serum from T1D patients, and to our knowledge it has not been reported by any other another study. For miR-151, it seems likely that this miRNA has a relation to metabolic processes, since it has been connected to mitochondrial activity [227], and decreased serum levels of both miR-151a-3p and -5p have been demonstrated after exercise [228].…”
Section: Mirnas Associated To Glucose Homeostasis Within the High-riscontrasting
confidence: 65%
“…Each miRNA can bind to multiple mRNAs, creating a complex regulatory network affecting many physiological and pathological processes [165][166][167]. In T1D, there are reports on differentially expressed miRNAs in PBMCs [168][169][170][171], and specific immune cell subsets like regulatory T cells [172]. There is also experimental data showing altered levels of miRNAs within the islets of NOD-mice during the pre-diabetic phase, and the expression of specific miRNAs was affected when exposing both murine-and human islets to pro-inflammatory cytokines [173].…”
mentioning
confidence: 99%
“…The study also showed that the miR-146 levels were associated with ongoing islet autoimmunity. 64 Moreover, miR-21a and miR-93 are decreased in PBMCs from T1D patients; 65 both miRNAs have been reported to participate in inflammatory and apoptosis signaling pathways 39 and are not affected by glucose stimuli. 65 Thus, the two miRNAs might be involved in the autoimmune responses of T1D.…”
Section: Mirnas: Regulators Of Immune Pathogenesis In T1dmentioning
confidence: 99%
“…63 Several possible target genes of miR-326, including vitamin D receptor and erythroblastosis virus E26 oncogene homolog 1, are vital modulators of the immune system, suggesting that the miRNA probably has important effects on autoimmunity in T1D by targeting these genes. 63 Another study performed by Yang et al 64 identified 26 differentially expressed miRNAs in PBMCs from newly diagnosed T1D patients, among which miR-146 was the most downregulated molecule. The study also showed that the miR-146 levels were associated with ongoing islet autoimmunity.…”
Section: Mirnas: Regulators Of Immune Pathogenesis In T1dmentioning
confidence: 99%
See 1 more Smart Citation